Prospect of bioprinted lungs for COVID-19 recovered patients - Rashid, MD Tawsif Ur; Noor, Mayesha (BRAC University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.